The Biography of Muḥammad : The Issue of the Sources - Motzki, Harald, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This book deals with the controversial value of the sources on which the biography of Muhammad, the founder of Islam, is based. Discussions on this topic have been going on for more than a century but it has become especially debated during the last two decades. This volume contains ten articles which are the outcome of an international colloquium on the issue. Part one of the book examines the development of the Muslim tradition concerning the life of Muhammad while the other part focuses on the historical reliability of the source material. The volume reflects not only the most recent methodological developments in the study of the life of Muhammad but also the improvement of its material-basis due to sources which have only recently become available or which have been neglected.